2007
DOI: 10.1016/j.canlet.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D provides a survival signal in human cancer cells with activated H-Ras or K-Ras

Abstract: Phospholipase D (PLD) is elevated in rodent fibroblasts expressing activated H-Ras mutants. We therefore examined the PLD activity in human cancer cells with activating Ras mutations. T24 bladder carcinoma cells express an activated H-Ras gene and Calu-1 lung carcinoma cells express an activated K-Ras gene. We report here that both of these cancer cell lines express highly elevated levels of PLD activity and that the PLD activity is dependent upon Ras. We also show that the PLD activity is dependent upon the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 36 publications
3
54
0
Order By: Relevance
“…Of significance, both mTOR and Raf have been implicated in human cancer. Consistent with this emerging role for PA in regulating cell proliferation, elevated expression and/or activity of enzymes that generate PA is commonly observed in human cancer, most notably phospholipase D (PLD) (5,6), which is elevated especially in K-Ras-driven cancers (7)(8)(9). Other enzymes that generate PA (lysophosphatidic acid (LPA) acyltransferase (LPAAT), and diacylglycerol (DG) kinase (DGK) (Fig.…”
Section: Phosphatidic Acid (Pa)mentioning
confidence: 61%
See 1 more Smart Citation
“…Of significance, both mTOR and Raf have been implicated in human cancer. Consistent with this emerging role for PA in regulating cell proliferation, elevated expression and/or activity of enzymes that generate PA is commonly observed in human cancer, most notably phospholipase D (PLD) (5,6), which is elevated especially in K-Ras-driven cancers (7)(8)(9). Other enzymes that generate PA (lysophosphatidic acid (LPA) acyltransferase (LPAAT), and diacylglycerol (DG) kinase (DGK) (Fig.…”
Section: Phosphatidic Acid (Pa)mentioning
confidence: 61%
“…We previously reported that in response to serum withdrawal there was a substantial increase in PLD activity in cancer cells (7), most notably in cancer cells harboring Ras mutations (9). More recently, we reported that PLD activity is also elevated in response to changing from medium with 10% serum to 10% delipidated serum (48).…”
Section: Compensatory Production Of Pa In Response To Metabolic Stresmentioning
confidence: 89%
“…MDA-MB-231 cells express a high level of phospholipase D (Zhong et al, 2003), which has been shown to specifically interact with PIP 3 , enhancing its anti-apoptotic activity (Ching et al, 1999). Loss of PIP 3 because of loss of PI3Kg activity would in turn lead to a loss of phospholipase D-dependent anti-apoptotic signaling (Yamada et al, 2004;Shi et al, 2007). Likewise, accumulation of active Akt also has anti-apoptotic effects by upregulating transcription factors that constitutively activate survival genes (Nicholson and Anderson, 2002;Osaki et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TSC and PLD are both modulated by mitogens (e.g., serum and insulin) [40][41][42][43][44][45][46] and TNFα. 15,47 The Ras-Raf-MEK-Erk pathway inhibits TSC2 via phosphorylation by either Erk 48,49 or a downstream kinase Rsk, 50 at the same time PLD activation by Ras [51][52][53][54] or Erk 54,55 has also been suggested. Most recently, our studies have uncovered a direct interaction between Rheb and PLD1.…”
Section: Pld1 As An Effector Of Rheb In Mtorc1 Signalingmentioning
confidence: 99%